Acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface for the diagnosis of compensated liver cirrhosis - Pfeifer, Lukas; Görtz, Rüdiger; Sturm, Jörg; Wachter, David; Riener, M. O.; Schwitulla, Judith; Bernatik, T.; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2014)
To evaluate the diagnostic value of acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface, using histology as a gold standard for the diagnosis of compensated liver cirrhosis.73 patients without ascites undergoing liver biopsy were included in the study. The left and right liver lobes were examined with ARFI and high-frequency ultrasound. Liver surface irregularity was quantified using image analysis software to calculate the difference between the real surface and the approximated physiological surface through a 20 mm standardized line.There is a significant difference between cirrhotic and non-cirrhotic patients for both quantified liver surface (QLS) and ARFI (p < 0.001). The mean values for QLS of the left lobe were 0.71 ± 0.24 mm and 1.17 ± 0.80 mm, of the right lobe 0.56 ± 0.26 mm and 0.87 ± 0.26 mm for non-cirrhotic and cirrhotic patients, respectively. The mean values of ARFI measurements of the left lobe were 2.04 ± 0.76 m/s and 2.85 ± 0.81 m/s, of the right lobe 1.65 ± 0.61 m/s and 3.02 ± 0.77 m/s for non-cirrhotic and cirrhotic patients, respectively. Diagnostic accuracy (AUROC) was 0.78/0.80 for QLS and 0.77/0.91 for ARFI of the left/right lobe, respectively. ARFI of the right lobe is significantly better than ARFI of the left (p = 0.023) or QLS of the left (p = 0.025)/right (p = 0.046) lobe of the liver.Assessment of liver surface irregularity by high-frequency ultrasound (QLS) is a useful diagnostic test for the assessment of compensated liver cirrhosis. ARFI of the right liver lobe is significantly better than high-frequency ultrasound (QLS of the left/right lobe of the liver) and ARFI of the left lobe of the liver.
EVALuna2:1858